Tolerance as the Way of Love: An Analysis of the Thought of Haidar Bagir and Habib Ja'far in the Indonesian Context - Riska Sasmita; Nurfadil (Pascasarjana IAIN Metro, 2025)
This paper analyzes the thoughts of Haidar Bagir and Habib Ja'far regarding tolerance as a way of love in the context of a multicultural and multireligious Indonesian society. The research method used is descriptive qualitative with a hermeneutic phenomenological approach, which focuses on analyzing the texts, lectures, and writings of the two figures. The purpose of this research is to understand how the idea of tolerance can be applied in facing the challenges of diversity in Indonesia. The results of the analysis show that Haidar Bagir emphasizes the importance of love as the foundation of tolerance, which must start from individual awareness, while Habib Ja'far invites people to prioritize compassion in interfaith interactions. Although the thoughts of both figures offer constructive solutions, challenges such as radicalization, the spread of hoaxes, and identity politics still hamper efforts to build tolerance. The conclusion of this study confirms that tolerance as a way of love is not just a concept, but a real action that must be realized in everyday life, with the support of various elements of society to create harmony in Indonesia.